AB0667 Anxiety-Depressive Spectrum and Cognitive Disorders in Behcet's Disease Patients. (9th June 2015) - Ishchenko, D.; Alekberova, Z.; Veltishchev, D.; Lisitsyna, T.A.; Seravina, O.; Kovalevskaya, O.; Novikov, A.; Alexandrova, E.; Krasnov, V.; Nasonov, E.
Abstract : Background: Psychiatric disorders (PD) of anxiety-depressive spectrum occur in Behcet's Disease (BD) patients quite often. The multifactorial genesis of PD in BD have not been clarified yet Objectives: To analyze the occurrence rate of PD and their associations with BD clinical features Methods: 75 patients with BD were enrolled in the study. All the patients met the criteria of the International Study Group for BD (1990). 57 (76%) patients were men and 18 (24%) – women, with a mean age of 33, 4±1, 15 (M±m) and mean disease duration of 150, 8±11, 9 months. Most of BD patients (46 (61, 3%)) were the inhabitants of the North Caucasus and parts of Western Asia: 24 (32%) were the natives of Daghestan, 10 (13, 3%) – the Chechens, 8 (10, 7%) - the Armenians, 4 (5, 3%) - the Azerbaijanians. 13 (17, 3%) were Russians. The disease activity was assessed by scoring system BDCAF. 73% of BD patients had a moderate and high activity of disease (BDCAF>3). 67 (75%) patients were taking prednisone in mean dose 9, 4±0, 68 mg/day (M±m), 66 (88%) - cytotoxic drugs. PD were diagnosed by psychiatrist in accordance with the ICD-10 in semi-structured interview. Psychiatric and psychological scales and methods used: Hospital Anxiety and Depression Scale for screening, Hamilton Anxiety Rating Scale, Montgomery-Asberg Depression Rating Scale (MADRS) and projective psychological methods for evaluation of cognitive functions. The severity of fatigue was evaluated with the Fatigue Severity Scale (FSS) Results: Anxiety-depressive disorders were diagnosed in 63 (84%) BD patients. Chronic depression prevailed - dysthymia was found in 22 (29, 3%) and recurrent depressive disorder - in 21 (28%) of BD patients. Single depressive episode had 9 (12%) patients, adjustment disorder - 7 (9, 3%), generalized anxiety disorder - 4 (5, 3%). Mild and moderate cognitive disorders were found in 62 (83%) BD patients. 61 (81, 3%) patients had acute stress events one year before the BD onset. The chronic psychosocial stress had 67 (89, 3%) BD patients. Early traumatic childhood experiences revealed in 46 (61, 3%) BD patients. The patients with anxiety-depressive spectrum disorders did not differ significantly on the age, duration of BD, gender, disease activity (BDCAF score) and BD clinical features from the patients without PD. The patients with major depressive disorder (MDD) had the high hsCRP level (>10 mg/l) two times more frequent (33, 3% vs 16, 6%) than the patients without PD. We found significant (p<0, 05) positive correlation between cognitive impairments and BD duration (r=0, 233), BDCAF score (r=0, 258), fibrinogen level (r=0, 481), anxiety-depressive spectrum disorders (r=0, 280) and chronic stress (r=0, 233), depression (MADRS score) (r=0, 304) and fatigue (FSS score) (r=0, 320) severity Conclusions: The results showed high occurrence rate of anxiety-depressive spectrum disorders and cognitive impairments in BD patients. The stress events preceded the BD onset and accompanied BD in majority of patients. MDD was associated with high hsCRP level, cognitive impairments - with BD activity and duration, anxiety-depressive spectrum disorders and chronic stress Disclosure of Interest: None declared